Isolation, characterization, identification and antimicrobial susceptibility testing of bacteria associated with pharmaceutical waste water treatment - Sharfin, Shah (BRAC University, 2018)
This dissertation is submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology 2016.